Comparative analysis of ITS1 nucleotide sequence reveals distinct genetic difference between Brugia Malayi from Northeast Borneo and Thailand - Fong, M.Y.; Noordin, R.; Lau, Y.L.; Cheong, F.W.; Yunus, M.H.; Idris, Z.M. (2012)
Brugia malayi is one of the parasitic worms which causes lymphatic filariasis in humans. Its geographical distribution includes a large part of Asia. Despite its wide distribution, very little is known about the genetic variation and molecular epidemiology of this species. In this study, the internal transcribed spacer 1 (ITS1) nucleotide sequences of B. malayi from microfilaria-positive human blood samples in Northeast Borneo Island were determined, and compared with published ITS1 sequences of B. malayi isolated from cats and humans in Thailand. Multiple alignment analysis revealed that B. malayi ITS1 sequences from Northeast Borneo were more similar to each other than to those from Thailand. Phylogenetic trees inferred using Neighbour-Joining and Maximum Parsimony methods showed similar topology, with 2 distinct B. malayi clusters. The first cluster consisted of Northeast Borneo B. malayi isolates, whereas the second consisted of the Thailand isolates. The findings of this study suggest that B. malayi in Borneo Island has diverged significantly from those of mainland Asia, and this has implications for the diagnosis of B. malayi infection across the region using ITS1-based molecular techniques.